Improving Motivation to Recover in Drug Abuse Victims Through Group Counseling Using the Modeling Symbolic Technique - Maulida, Aisyah; Saputra, Randi; Barriyati, Barriyati (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2024)
The purpose of this study was to determine the steps of group counseling using the symbolic modeling technique; the level of motivation to recover among drug abuse victims after receiving group counseling using the symbolic modeling technique; and the increase in motivation to recover among drug abuse victims after receiving group counseling services using the symbolic modeling technique. This study used the Guidance Counseling Action Research (PTBK) method. The primary sources were residents at the Rumah Rahayu Rehabilitation Foundation, while the secondary sources were personnel or staff at the Rumah Rahayu Rehabilitation Foundation. The results of this study show that the motivation of drug abuse victims before receiving group counseling through the symbolic modeling technique, as seen from the questionnaire results, was low for four residents. The percentage of motivation levels before group counseling was 100% of residents in the low category. However, after providing group counseling services through the symbolic modeling technique, there was an increase as seen from the questionnaire results, namely 4 residents in the very good category with a percentage of 73% in cycle 1 and 82% in cycle 2.